REVIEW : Mangrove ecosystem in Java: 2. Restoration - AHMAD DWI SETYAWAN; KUSUMO WINARNO; PURIN CANDRA PURNAMA (Society for Indonesian Biodiversity, 2004)
The restoration of mangroves has received a lot of attentions world wide for several reasons. Mangrove ecosystem is veryimportant in term of socio-economic and ecology functions. Because of its functions, wide range of people paid attentionwhenever mangrove restoration taken place. Mangrove restoration potentially increases mangrove resource value, protect the coastal area from destruction, conserve biodiversity, fish production and both of directly and indirectly support the life of surrounding people. This paper outlines the activities of mangrove restoration on Java island. The extensive research has been carried out on the ecology, structure and functioning of the mangrove ecosystem. However, the findings have not been interpreted in a management framework, thus mangrove forests around the world continue to be over-exploited, converted to aquaculture ponds, and polluted. We strongly argue that links between research and sustainable management of mangrove ecosystem should be established.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: mangrove, restoration, management, Java.